Faktor-faktor yang mempengaruhi tunggakan pajak kendaraan bermotor Kabupaten Tanjung Jabung Barat (studi kasus: Kecamatan Tungkal Ilir) - Eymilia Oktavia; Muhammad Safri; Yohanes Vyn Amzar (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
This study aims to determine and analyze: 1) the characteristics of PKB arrears in terms of age, education level, income, and motor vehicle tax service system (PKB) in Tungkal Ilir District and 2). The influence of age, education level, income, and motor vehicle tax service system (PKB) on motor vehicle tax arrears in Tungkal Ilir District. The data analysis method used in this study used descriptive analysis and regression analysis, models. Based on the results of the study, it was obtained: years, the average level of education of respondents is SMA / equivalent and the average monthly income/income is Rp. 2,486,000. Age (U) has a positive and significant effect on motor vehicle tax arrears, while education level (TP), income (P), and tax service system (SP) have a negative effect. and significant to the Motor Vehicle Tax arrears in Tungkal Ilir District, either jointly or partially. Keywords: Tax arrears, Motor vehicles, Multiple regression analysis